Peran Komunikasi Antar Pribadi Guru dan Anak Dalam Mencegah Kenakalan Remaja di SMA Negeri 2 Binjai - Hidayat, Taufik; Sumanti, Solihah Titin (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
A teacher must also be clever in choosing communication in approaching students (in terms of learning and counseling). In this case, of course interpersonal communication is best used in carrying out this communication. With persuasive and effective interpersonal communication between teachers and students, it is hoped that it will help motivate, mobilize and encourage students to be more active in studying, and can help change a student's behavior, attitude and good thinking patterns. This research method uses a qualitative research approach with a descriptive approach. This research shows that the existence and implementation of face-to-face communication (interpersonal communication) without realizing it will establish good relationships between teachers and students without erasing respect and feelings of respect for the teacher. Students become brave enough to speak up when they have difficulties either regarding their studies or personally, and teachers become able to accept any student complaints regarding lessons and any difficulties they experience. Keywords: Role, Interpersonal Communication, Juvenile Delinquency